Genome-Wide Identification and Analysis of the NF-Y Gene Family in Potato (Solanum tuberosum L.) - Liu, Zhen; Li, Yuanming; Zhu, Jinyong; Ma, Wenjing; Li, Zhitao; Bi, Zhenzhen; Sun, Chao; Bai, Jiangping; Zhang, Junlian; Liu, Yuhui (Frontiers in Genetics, 2021)
Nuclear factor Y (NF-Y) is a ubiquitous transcription factor in eukaryotes, which composed of three subunits (NF-YA, NF-YB, and NF-YC). NF-Y has been identified as a key regulator of multiple pathways in plants. Although the NF-Y gene family has been identified in many plants, it has not been reported in potato (Solanum Tuberosum). In the present study, a total of 41 NF-Y proteins in potato (StNF-Ys) were identified, including 10 StNF-YA, 22 StNF-YB, and nine StNF-YC subunits, and their distribution on chromosomes, gene structure, and conserved motif was analyzed. Collinearity analysis showed that nine pairs of duplication genes played an important role in the expansion of the StNF-Y gene family. The expression of StNF-Y genes in different tissues, under abiotic stresses and hormone treatments in MD potato was analyzed according to RNA-seq data. Furthermore, we analyzed the expression of StNF-Y genes in tetraploid pigmented potato cultivars based on RNA-seq data and constructed a protein interaction network to further identify StNF-Y proteins that might be related to anthocyanin biosynthesis. These results provide valuable information for improved understanding of StNF-Y gene family and further functional analysis of StNF-Y genes in fruit development, abiotic stress tolerance, and anthocyanin biosynthesis in potato.